CLINICAL PROFILES OF PATIENTS ATTENDING TO OSTEOPOROSIS CENTER OF GRAND HANTHA INTERNATIONAL HOSPITAL (GHIH) - Myint, Kyar Nyo Soe; Aye, Than Than; Thet, Kyaw Swar (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Osteoporosis is the most common chronic metabolic bone disease, which is characterized by increased fragility fracture. We aim to describe the clinical profiles of osteoporosis/osteopenia patients seen at the Osteoporosis Center of Grand Hantha International Hospital (GHIH) and evaluate DXA scan results amongst fractures in our center. METHODOLOGY This study is a retrospective analysis of the clinical characteristics of 137 participants above 40 years old who were referred to or directly entered into the Osteoporosis Center of GHIH from October 31, 2022 to July 14, 2023. Osteoporosis was analyzed using the WHO T-score criteria through DXA scanning, and fracture risk was calculated using the FRAX calculation method. RESULTS Among the 137 patients enrolled in the clinic, 117 patients have either osteoporosis in at least one site according to the T-score, or a major osteoporotic fracture risk (MOF) greater than 20% or a hip fracture risk greater than 3% by FRAX calculation. The remaining 20 patients neither haveosteopenia nor an increased risk of fracture. In terms of gender distribution, 89.1% of the attendees were female patients, while 10.9% were male. The mean age of the patients is 72 years (SD 11.0), with a range from 44 to 108 years. The mean age of the fracture group is 75.69 (SD 11.21), while that of the non-fracture group is 70.43 (SD 10.6). There is a significant difference in age between the two groups (p = 0.009), with the fracture group being older. Among the patients, 72.9% have one or more underlying diseases, type 2 diabetes (59%) being the most common associated disease.Regarding fragility fractures, 32.0% of female patients and 26.7% of male patients have recently experienced a fracture, but there is no significant association between genderand fracture occurrence (p = 0.776). BMI distributions areas follows: underweight (5.1%), normal weight (29.9%), overweight (18.2), and obese (35.8%). The mean BMI of the fracture group is 25.56 (SD 6.629), while that of the nonfracture group is 23.89 (SD 4.206). There is no significant association between BMI and fragility fractures (p = 0.098). Among the 122 patients who had T-scores from DXA results, a minor discordance in T-scores was found in 48 patients (45.5%), which was defined as the lumbar spine T-score is below -2.5 but the hip T-score is between -1 and -2.4. Although there were 117 osteoporotic patients, only 104 of them received treatment. The most commonly used drug for treatment is oral bisphosphonates (32.8%), followed by SC Denosumab, IV zoledronate, and SC teriparatide. CONCLUSION This study demonstrates that for those identified to have osteoporosis in this institution, females predominate, and the majority of the attendees have one or more underlying diseases, with type 2 diabetes being the most common associated disease. Osteoporotic fracture is not associated with gender or BMI but is associated with aging. Oral bisphosphonates were the most commonly prescribed drug for osteoporosis in the study patients.